Contribution of epicardial adipose tissue to atrial fibrillation development in patients with arterial hypertension: a pilot study - S. V. Miklishanskaya; N. A. Mazur; A. V. Chapurnykh; M. A. Saidova; O. Ya. Narusov; S. A. Orlovsky (Российский кардиологический журнал)
Aim. To evaluate the value of body mass index (BMI), visceral adipose tissue (VAT) and epicardial adipose tissue (EAT) depots in the development of atrial fibrillation (AF).Material and methods. The study included 24 people with isolated hypertension (HTN) and 28 people with HTN in combination with AF. The median age of patients was 61,5 [53,8;69,0] years. The observational study assessed height, weight, BMI, proportion of VAT, EAT thickness, and cardiac chamber sizes. Height was measured using a metal height meter Rm-1 "Diakoms"; the results were expressed in centimeters. Weight, BMI, and VAT proportion were measured using an Omron BF-508 body composition monitor (Omron, Japan). EAT thickness and cardiac chamber sizes were assessed using two-dimensional echocardiography. Univariate logistic regression models were used to assess the independent contribution of the identified factors associated with the disease presence.Results. Hypertensive patients with and without AF were comparable in terms of BMI and VAT content. At the same time, the EAT content was significantly higher in the group of patients with HTN and AF and amounted to 7,0 [5,0;8,2] mm and 6,0 [4,5;7,0] mm (p=0,027) in the group HTN with and without AF, respectively.Left atrial (LA) volume was 70 [55,2;83,0] ml and 52 [45,5;59,0] ml (p=0,003) in the hypertensive group with and without AF, respectively. Univariate analysis revealed the greatest significance of EAT and LA volume in terms of AF prediction. Logistic regression models did not reveal significant effect of VAT.Conclusion. In hypertensive patients with and without AF at comparable levels of BMI and VAT, differences in EAT thickness and LA volume were identified. Univariate analysis showed that these factors have an advantage in the development of AF. However, even despite the limited sample, the EAT depot was found to be more significant than the VAT depot and BMI in predicting the AF risk.The data that EAT depot and LA volume have the same effect on the arrhythmia risk indicates that patients with AF should be treated not only for hypertension, but also hidden obesity, which we can judge by EAT thickness.